Rumen protozoal population and fermentation pattern as affected by all roughage diet in goats - CHAUDHARY, U B; SINGH, NAWAB (The Indian Journal of Animal Sciences, 2014)
An altempt was made to assess the impact of all roughage diet on rumen protozoal population anq fermentation pattern in goals. Adult male goats (10) of Barbari breed having average body weight of 35.12Â±2.53 kg were fed gram straw and berseem ad lib. and 250 g of pelleted concentrate feed under treatment A. After the feeding of 25 days these animals were switched over to treatment B and were offered the same diet for 25 days as in treatment A, except pelleted feed which was withdrawn in treatment B. Results revealed significantly (P< 0.05) higher total dry matter and crude protein intake in treatment B in comparison to treatment A. The ammonia nitrogen and total volatile fatty acid in the rumen liquor were also significantly (P< 0.05) higher under treatment B where as lower ciliate population was observed in treatment B. Higher values of butyrate were noted under treatment A in comparison to treatment B. Ciliate popUlation in both the treatments was represented by A-type. Decline in the population of holotrichs was observed comparatively less by 35.35% than entodinomorphs where reduction was observed to be 54.14%. Amongst all the ciliate species the maximum fall in the population was observed in Entodinium elongatum (83.96%). Complete disappearance of Ohryoscolex purkynei specie was observed in treatment B although the population of this specie was also very thin in treatment A. Observations collected at 0 and 4 hr of feeding intervals revealed lower values of ciliate population, pH and ammonia nitrogen at 0 hr, however, the higher values of volatile fatty acid production in the rumen liquor were recorded at 4 hr of feeding interval. Concentration of propionate and acetate was recorded significantly higher (P< 0.05) and lower at 4 hr of feeding in . comparison to 0 hr respectively. Except, Enoploplastron friloricatum and Dip/odinium dentatum the population of all the ciliate species reduced at 4 hr of post feeding in comparison to 0 hr Dip/odinium dentaum at 0 hr. Therefore dry matter intake through roughage, total volatile fatty acid production, ammonia and acetate production were higher in trcatment B and ciliate population, pH and butyrate production were higher on concentrate supplemented diet indicating better fermentation pattern in all roughage dieL Thus all roughage diet was in no way inferior to concentrate diet rather it may also be economical.